The association of subepithelial connective tissue graft and enamel-derived matrix in the covering of gingival recessions (Research, Society and Development, 2021)
Gingival recession (GR) can be defined as a condition in which migration occurs in the apical direction with consequent exposure of the cementoenamel junction and root surface. Periodontal plastic surgical techniques aim to improve the gingival phenotype and correct the morphology, position and dimensions of the gingival tissue. In recent years, in order to improve the results of these treatments, new resources related to the optimization of periodontal regeneration have been associated with gingival grafts. Whether or not it is an adjunct to surgical techniques for root coverage, the enamel-derived matrix (Emdogain â) has been increasingly incorporated into these treatments, as both its clinical applicability and its benefits are already supported. in scientific evidence. The aim of this study is to carry out an integrative literature review on the use of enamel-derived matrix (EMD) in periodontal plastic surgical procedures for the treatment of gingival recession. For the elaboration of the study, the PICO strategy and the search in the PubMed, MedLine and Scielo databases were used, using the following keywords: “enamel matrix derivatives”, “gingival retraction” and “subepithelial connective tissue graft”. From this search, 181 articles published between the years 2016 to 2021 were selected, and of this number, only 12 were used to perform the literature review. With this review, it was possible to conclude that EMD associated with subepithelial connective tissue grafts can increase the predictability of the covering therapy, which may favor a new periodontal insertion.